PENDIDIKAN AKHLAK REMAJA DI ERA DIGITAL: IMPLEMENTASI FILSAFAT PENDIDIKAN ISLAM DI SEKOLAH DAN KELUARGA - Rahma Dilla Zainuri; Iyad Suryadi; Helmawati; Haerudin; Mitra Sasmita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The digital era has brought significant changes to adolescents’ lives, particularly in patterns of interaction, behavior, and moral development. Easy access to information and the intensive use of digital media offer opportunities while simultaneously posing serious challenges to adolescents’ moral education. This article aims to examine the implementation of Islamic educational philosophy in adolescents’ moral education within school and family environments in the digital era. This study employs a qualitative approach using a library research method by analyzing relevant literature on Islamic educational philosophy, moral education, and education in the digital era. The findings indicate that the core values of Islamic educational philosophy—such as tawhid, the balance between reason and revelation, the integration of faith and knowledge, and the orientation toward the formation of insan kamil—remain highly relevant in fostering adolescents’ moral character. The implementation of these values can be realized through the role modeling of teachers and parents, the internalization of moral values in the learning process, the habituation of positive behavior, and the strengthening of digital literacy based on Islamic ethics. Therefore, synergy between schools and families grounded in Islamic educational philosophy constitutes a strategic key to shaping adolescents with strong character and ethical awareness in the digital era.